Efficiency Analysis of Specialty Construction Companies by Industry and Year Using DEA Model - Dae-Woon, Jung; Kyung-Rai, Kim (Journal of the Architectural Institute of Korea, 2023)
This study utilized the DEA model to analyze the efficiency of various specialty construction industries. Data from 2017 to 2021, covering 520 specialty construction companies, were examined. The findings indicated that these companies were inefficient in terms of scale, highlighting the need for improvements through measures like reducing production factors, such as scale reduction. Among the specialty construction industries, the reinforced concrete construction sector demonstrated significantly higher efficiency compared to others, emphasizing the importance of benchmarking between these industries. The outbreak of the COVID-19 pandemic resulted in a temporary decline in efficiency within the specialty construction industry in 2020, but a recovery was observed in 2021. However, operating profit efficiency saw a substantial decline in 2021, primarily due to soaring raw material prices. Consequently, it was deduced that the increase in sales efficiency resulted from these price surges. The study identified the reinforced concrete construction industry of metal, window, roofing, prefabrication construction, and painting, wetting, waterproofing of the stone construction industry as most impacted by escalating construction material costs. Therefore, it is crucial for specialty construction companies to enhance efficiency by reducing input factors, with a specific focus on efficiency management strategies considering rising raw material prices for the aforementioned industries. It is important to note that this study only analyzed specialty construction companies subject to external audits, and factors like technological changes were not considered. The analysis primarily focused on relative efficiency within the same industry category.
Keywords: Data Envelopment Analysis (DEA); Efficiency; Industry of Specialty Construction; Specialty Construction Company